2017
DOI: 10.1186/s12882-017-0589-3
|View full text |Cite
|
Sign up to set email alerts
|

Modern peptide biomarkers and echocardiography in cardiac healthy haemodialysis patients

Abstract: BackgroundIn this prospective study, we aimed to assess the haemodynamic changes before and after haemodialysis (HD) in cardiac healthy subjects on chronic HD by imaging methods and endocrine markers of fluid balance.MethodsMid-regional pro-atrial natriuretic peptide (MR-proANP), N-terminal prohormone of brain natriuretic peptide (NT-proBNP), vasopressin (AVP) and copeptin (CT-proAVP), metanephrines and normetanephrines, renin and aldosterone, standard transthoracic echocardiography and diameter of vena cava i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…In our study, plasma copeptin correlated with renal Kt/V but not with peritoneal Kt/V, suggesting that kidneys play a major role in the elimination of copeptin. Similar to Rasche et al [26], we did not find a significant association of copeptin with age or gender.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, plasma copeptin correlated with renal Kt/V but not with peritoneal Kt/V, suggesting that kidneys play a major role in the elimination of copeptin. Similar to Rasche et al [26], we did not find a significant association of copeptin with age or gender.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, Rasche et al showed that plasma copeptin levels, which were approximately 11-fold higher in hemodialyzed patients compared to normal population, decrease during the hemodialysis (HD) session. The relative reduction of copeptin during HD correlated inversely with the Kt/V ratio, indicating that copeptin might be eliminated by HD [26].…”
Section: Discussionmentioning
confidence: 99%